2015
DOI: 10.1111/pce.12535
|View full text |Cite
|
Sign up to set email alerts
|

AtLa1 protein initiates IRES‐dependent translation of WUSCHEL mRNA and regulates the stem cell homeostasis of Arabidopsis in response to environmental hazards

Abstract: Plant stem cells are hypersensitive to environmental hazards throughout their life cycle, but the mechanism by which plants safeguard stem cell homeostasis in response to environmental hazards is largely unknown. The homeodomain transcription factor WUSCHEL (WUS) protein maintains the stem cell pool in the shoot apical meristem of Arabidopsis. Here, we demonstrate that the translation of WUS mRNA is directed by an internal ribosomal entry site (IRES) located in the 5'-untranslated region. The AtLa1 protein, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…The vast majority of IRESmediated translation events have been described in metazoans, and, in plants, cap-independent elements are found in viral transcripts that often lack the cap structure (Miller et al, 2007). Although the evidence of classic IRESs in plant genomes is poor, there are some examples of endogenous plant cytoplasmic mRNAs being translated through IRES-like mechanisms (Dinkova et al, 2005;Cui et al, 2015).…”
Section: Internal Ribosomal Entry Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of IRESmediated translation events have been described in metazoans, and, in plants, cap-independent elements are found in viral transcripts that often lack the cap structure (Miller et al, 2007). Although the evidence of classic IRESs in plant genomes is poor, there are some examples of endogenous plant cytoplasmic mRNAs being translated through IRES-like mechanisms (Dinkova et al, 2005;Cui et al, 2015).…”
Section: Internal Ribosomal Entry Sitesmentioning
confidence: 99%
“…Furthermore, WUS contains an IRES in its 5 0 UTR. Thus, it was not a total surprise when it was found that under environmental stress a fraction of AtLa1 protein moves to the cytoplasm, where it binds to the 5 0 UTR of WUS and increases its IRES-dependent translation (Cui et al, 2015). This mechanism may have evolved to ensure the proper translation of essential genes, such as WUS, in the maintenance of meristem under stress-conditions when cap-dependent translation is downregulated.…”
Section: Translation Regulation Mediated By Structural Features Of Thmentioning
confidence: 99%
“…We thank Bruno Müller (University of Zurich, Switzerland) for kindly providing pTCSn::GFP , Tao Huang (Xiamen University, China) for kindly providing pWUS::GFP ‐ GUS , pCLV3::GFP ‐ GUS (Cui et al ), and the Nottingham Arabidopsis Stock Centre for the arr12‐1 (CS6978) mutant and pARR12::GUS (N25395). This research was financially supported by the National Special Science Research Program of China (grant no.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Thus, execution of the redox‐sensing and signalling cascades adjust plant growth and development in accordance with the newly imposed redox state (Fernández‐Marcos et al ; Scheibe & Dietz ; Tognetti et al ; Considine & Foyer ; Del Río ; Xia et al ). Increased ROS and NO production under stress, for example, influences plant growth and development by, amongst other means, affecting auxin and cytokinin networks, which have long been known as key players in the formation and maintenance of meristems (Su et al ; Cui et al ; Diaz‐Vivancos et al ; Schaller et al ).…”
Section: Introductionmentioning
confidence: 99%